Canva-based Smart Apps Creator Media to Enhance Comprehension Skills of Informational Text for Third-Grade Students - Al Haq, Ghaida Tsurayya; Sismulyasih SB, Nugraheti; Purwati, Panca Dewi (International Journal of Elementary Education, 2024)
Learning media, as a tool for delivering information from teachers to students, aims to facilitate the teaching and learning process in school. Smart Apps Creator is a software with several advantages for developing interactive learning media, one of which is with the assistance of Canva application as its online design application. This research aims to create Canva-based Smart Apps Creator media to enhance the ability to understand the content of information texts in third-grade elementary schools. The research method used is Research and Development (R&D) based on Sugiyono's research with the Borg & Gall development model modified into eight stages, namely: potential and problems, data collection, product design, design validation, design revision, product testing, product revision, and usage testing. This research utilizes data collection techniques through tests and non-tests. The data analysis techniques used include both qualitative and quantitative data analysis. The material expert validation result obtained a percentage of 90%, and the media expert validation obtained a percentage of 92%, both categorized as "highly feasible." Using Canva-based Smart Apps Creator media in learning activities is quite effective through N-gain testing, with students' learning outcomes reaching 0.66 (65.6%), and the average pre-test score increased from 55 to 83 during the learning process (post-test). From these results, the Canva-based Smart Apps Creator media is declared highly suitable for learning and sufficiently effective in improving the ability to comprehend the content of information texts in Indonesian language classes for third-grade elementary school.